Critical Chain Project Management for Hospital Reconstruction: Cost and Time Optimization - Berlinda Alveria Agusta; Hanie Teki Tjendani; Buntara Sthenly Gan (jfpublisher, 2026)
Construction project delays represent a persistent challenge in Indonesian infrastructure development, with delay rates reaching 38% and causing substantial cost overruns and quality compromises. This research evaluated the application of Critical Chain Project Management methodology to optimize cost and time performance in the Undata Hospital Phase II-B Rehabilitation and Reconstruction Project in Palu, Central Sulawesi, which experienced significant delays from 240 contracted days to 426 actual implementation days. Using Microsoft Project for critical chain identification and Root Square Error Method for buffer calculation, the study analyzed 228 structural work activities to determine schedule optimization potential. Results identified nine critical chain activities concentrated in foundation work, requiring 60-day project buffer and 36-day feeding buffer allocation. CCPM application achieved 159-day duration reduction (43.1% improvement) compared to actual implementation, reducing total duration from 369 days to 210 days. Economic analysis revealed potential labour cost savings of IDR 7,398,931,383.36 (59.0% reduction) through elimination of embedded safety time and strategic buffer placement. Comparative evaluation demonstrated that traditional scheduling dispersed 183 days of safety time across individual activities, manifesting as work expansion through Parkinson's Law effects. Even under partial buffer consumption scenarios, CCPM maintained substantial performance advantages, confirming methodology robustness. These findings support CCPM adoption for Indonesian reconstruction projects requiring complex coordination, extended durations, and strategic schedule management under international funding frameworks.